Negotiating the Religious in Contemporary Everyday Life in the "Islamic World" - Loimeier, Roman (Universitätsverlag Göttingen, 2021)
The contributions to the present volume show that the countries that are often presented in the literature as forming part of a stereotypical and seemingly monolithic "Islamic world" in fact represent considerable diversity. From Iran to Senegal, we encounter a vast array of social and religious structures, historical trajectories, political regimes and relative positions of societies and individuals. We encounter also, in many different and often unexpected ways, the individual in multiple contexts. The present volume presents perspectives on everyday life in Muslim societies beyond the spectacular. From a broad academic background in Islamic and Iranian studies, social anthropology, sociology, philosophy and history, its contributors show that everyday life as well as religious practice in countries as diverse as Senegal, Niger, Egypt, Tunisia and Iran is not informed by one single "Islamic" tradition, but rather by multiple and often surprisingly different modes of religiosity and non-religiosity.